A mixed integer nonlinear programming model for the optimal repair–replacement in the firm - Motamedi, N.; Reza Peyghami, M.; Hadizadeh, M. (Mathematical social sciences, 2013)
Optimal repair–replacement problem is an important aspect of economic decision making at the firm and aggregate levels. In this paper, we extend the continuous time optimal replacement model in the firm under technological progress by considering the possibility of repairing/replacing the machines during their lifetime period. In our model, two possible decisions can be recognized by the managers in which the machines are repaired under the efficiency condition or replaced under the availability of technological progress in the firm. As a special case, we restrict the model to the more real case in which all the growth, purchase price and repair cost functions are assumed to be in the exponential form. The solvability of the model in this case is also discussed. •Proposing an optimal repair–replacement model in firms under technological change.•Construction of a mixed-integer programming to the new repair–replacement model.•Investigating the optimality and solvability of the model under some assumptions.•More discussions on the solvability of the new model in a specific case in economic.•Providing an approach for solving the specific case of new proposed model.